Evaluating Malaysian Palm Oil Industry using Discounted Cash Flow Approach - Sharon Rebecca Tan; Hiram Ting; Nelson Lajuni; Yusman Yacob; Joseph Wee-Siong Hii (2018)
This research is a case study involving an oil palm plantation company (Case Company) which owns seven oil palm plantations. These seven plantations had all been valued by Licensed Property Valuers (LPV) who used the market comparison method. The research study applies the Discounted Cash Flow Method (DCF Method), a quantitative financial model as a business valuation method, to value the seven plantations. This research study starts out by looking for an alternative or comparative business valuation method so that it can be used as an additional valuation tool in the loan credit evaluation process, in addition to the LPV valuation. The test results show the two sets of values to be significantly similar. The results of the study supported the DCF Method for valuation for the palm oil plantations. This finding is important because it is of tremendous benefit to both practitioners, especially, those in the banking industry, and the academia to have a financial business valuation model that can be used to enhance the loan credit evaluation process. This gives the confidence that the DCF Method can be considered to be used for valuation purposes for bank loan collaterals. However, because of some limitations of this research study, this study should be replicated for further studies to be conducted to further reaffirm the proposal for the DCF Method to be completely accepted as a business valuation approach for bank credit purposes.